Simulation of interaction between a freely moving solid particle and a freely moving liquid droplet by lattice Boltzmann method - Yang, Bo; Chen, Sheng (Elsevier, 2018)
Solid particles and liquid droplets widely coexist in many industrial processes. Particle-droplet interactions critically influence the dynamics of those processes. In this study, the interactions between a freely moving solid particle and a freely moving liquid droplet are numerically investigated using the lattice Boltzmann method. Until now the open literature on such topic is quite sparse. Through the present numerical investigation, two regimes to classify the interactions between a freely moving solid particle and a freely moving liquid droplet are proposed. In addition, it is found that the particle-to-droplet size ratio and particle’s wettability play critical roles in such interactions.